Kajian Persepsi Dan Perilaku Masyarakat Terhadap Pencemaran Air Sungai Martapura - Laila Rismawati; Bambang Joko Priatmadi; Achmad Syamsu Hidayat; Eko Rini Indrayatie (Universitas Lambung Mangkurat, 2020)
Many studies showed that rivers in Indonesia had been polluted. This is due to the large number of human activities, both from industrial, domestic, and agricultural waste. Kampung Sasirangan is one of the settlements located on the bank of Martapura River. The existence of industrial activities from sasirangan waste water and the large number of people deficating and throwing the garbage in the river causes water pollution. Good perceptions and good behavior is expected to increase community participation in river conservation. The purpose of this study was to determine the perceptions and behavior of the community regarding pollution that occurs in the Martapura River and to determine alternative strategies to control water pollution of Martapura River. Data was collected by questionnaires, observation, and interviews. The sample of respondents in this study used Slovin formula, amounted 100 respondents. This research use descriptive qualitative anaylisis. The results of this study show that most respondents have a poor perception of water pollution. Therefore, a strategy is needed that can make positive perceptions so that community behavior cares about environmental sustainability, that is education, wastewater treatmant plan, legislation, monitoring, and encouragement of public figure